Transforming Higher Education in Sub-Saharan Africa: Overcoming 21st- Century Challenges with Practical Remedies - Edoru, John Michael; Turyasingura, Benson; Kayusi, Fredrick; Juma, Linety; Mishra, Rashmi; Vallejo, Rubén González (Region Cientifica, 2025)
The aim of the study was to document the 21st-century challenges faced by Higher Education practitioners and to propose practical solutions. Section 62(3) of the Act (UOTIA) prohibits public universities from spending funds not approved by Parliament. This provision hampers universities’ progress in diversifying revenue streams and proactively raising funds, which ultimately impacts higher education. Furthermore, Section 59(5) of the Act (UOTIA) does not give universities the right to invest their funds without the approval of the line ministries. This requirement hinders researchers and other external funders, who may not be fully aware of the role of line ministries in approving the use of donor, grant, or research funds. Other challenges included: weak leadership and governance, financial constraints, curriculum relevance, and the digital divide. However, practical remedies such as leadership development programmes, modernizing curricula, investing in digital infrastructure, and promoting equity and inclusivity can help address these issues. This study supports the World Education 2030 Agenda, which advocates for inclusive and equitable education. The EU Education Agenda prioritizes lifelong learning, digital transformation, and research collaboration to address global challenges and promotes SDG 4 (Access to Quality Education) as well as promoting innovation, gender equality, and a sustainable economy. Therefore, governments and higher education institutions should invest in leadership development programmes aimed at strengthening governance structures.